Opresi dan Dinamika Maskulinitas Ajo Kawir dalam Seperti Dendam Rindu Harus Dibayar Tuntas (2014) - Nafis, Rafi Raihan (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2024)
Gender is a social construction, both men and women are affected by its hegemony. If women are constructed to be feminine, men are expected to masculine. Traditional masculinity is hegemonic that it forces men to have masculine quality, such as active, aggressive, dominant, heterosexual and not-feminine. In society, they fight in arena of masculinity to prove themselves as the true man. As a study of gender, feminism is only centered on the study of gender oppression to women or how masculinity is the source of such oppression. Consequently, gender oppression to men are often marginalized. This research fills the gap on the current trend of feminism literary critics by highlighting how masculinity can oppress men and how men (both writer and character in the novel) respond and adapt with this hegemonic traditional masculinity. This research uses Eka Kurniawan’s Seperti Dendam Rindu Harus Dibayar Tuntas (2014) as material object. This research found that traditional masculinity oppress Ajo Kawir: the sexual violence against him goes unnoticed and he has to constantly prove himself as a man through violence. In this novel, Ajo Kawir also shows the negotiation process with hegemonic masculinity in three different phases. As a writer, Eka Kurniawan tries to offer an alternative masculinity, but because masculinity is hegemonic, this alternative masculinity does not completely break the construction of traditional hegemonic masculinity. In his alternative there are aspects that are different from traditional masculinity and some that remain the same.